If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(3x + -9) = 0 Reorder the terms: 6(-9 + 3x) = 0 (-9 * 6 + 3x * 6) = 0 (-54 + 18x) = 0 Solving -54 + 18x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '54' to each side of the equation. -54 + 54 + 18x = 0 + 54 Combine like terms: -54 + 54 = 0 0 + 18x = 0 + 54 18x = 0 + 54 Combine like terms: 0 + 54 = 54 18x = 54 Divide each side by '18'. x = 3 Simplifying x = 3
| 7x+4=84 | | (x+6)+(x+2)+10+20=180 | | 5x+34=2x+13 | | -4(6.1x-5.4y-2z+9)= | | 3+2m=-7 | | 5-4k=21 | | 6x+8=3x+17 | | (x+8)+(x+5)+(3x-4)=180 | | r/10+4=5 | | 3x^2+47x=-30 | | 3x-x+14-8= | | 65+65+50+(x+10)=180 | | ax^3+bx=0 | | 4x^2+22x=0 | | 65+65+50+x+10=180 | | x-5x=30 | | 0.1x-1=5 | | 4x+22x=0 | | 14x^2+6x+50=0 | | x-5(x)=30 | | 49w^2-100= | | 2x-4=180 | | 45+99+36+5y-10=180 | | 8u^5v^3-12u^5v^4w^5= | | 47+8y+8+4y+5=180 | | (8t^8-6t^3+2t^2+9)+(7t^7+2t^3-5t)= | | -16t^2+48t+64= | | 47+4y+5=180 | | 9v^2-49= | | y=3x+17 | | 186=2l+2w | | 6c^3-4c= |